2005
DOI: 10.1002/ejoc.200500105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of an Unsymmetrical Triazole‐Functionalized (Phthalocyaninato)zinc Complex

Abstract: The synthesis of 5,6-dicyano-1H-1,2,3-benzotriazole (2) was significantly simplified and its overall yield was increased. This opens up the possibility for an extended use of 2 as a precursor for triazole-functionalized phthalocyanines. One of them, the unsymmetrical {9, 10,16,17,23,24-hexakis(3,5-ditert-butylphenoxy) [1,2,3]triazolo [4,5-b]phthalocyaninato}-zinc (5) was prepared in a statistical condensation of 2 and 4,5-bis(3,5-di-tert-butylphenoxy)phthalonitrile (3) with subsequent separation by column chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
(18 reference statements)
1
29
0
Order By: Relevance
“…These unsymmetrical Pc synthons have been used for the preparation of ethynyl‐substituted phthalocyanines, ethynyl‐ and diethynylethene‐bridged bis(phthalocyanines), binuclear and trinuclear phthalocyanine‐containing phosphonium salts, as well as for the synthesis of other important Pc synthons containing vinyl or aldehyde functionalities 3. Recently, we reported the preparation of a new unsymmetrical, soluble zinc‐phthalocyanine with one fused 1,2,3‐triazole ring in the periphery (compound 1 in Scheme ) 4. First investigations on the properties of 1 have shown that it is another useful synthon for various unsymmetrical modifications of phthalocyanines.…”
Section: Introductionmentioning
confidence: 99%
“…These unsymmetrical Pc synthons have been used for the preparation of ethynyl‐substituted phthalocyanines, ethynyl‐ and diethynylethene‐bridged bis(phthalocyanines), binuclear and trinuclear phthalocyanine‐containing phosphonium salts, as well as for the synthesis of other important Pc synthons containing vinyl or aldehyde functionalities 3. Recently, we reported the preparation of a new unsymmetrical, soluble zinc‐phthalocyanine with one fused 1,2,3‐triazole ring in the periphery (compound 1 in Scheme ) 4. First investigations on the properties of 1 have shown that it is another useful synthon for various unsymmetrical modifications of phthalocyanines.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Investigation of its spectral properties (UV/Vis, 1 H and 13 C NMR) revealed many similarities between 5 and 7.…”
Section: Resultsmentioning
confidence: 97%
“…UV/Vis spectroscopy: Shimadzu UV-365. 1 (1), [2] bis(4-tert-butylphenyl)fumaronitrile (A), [15] 5,6-dicyano-1H-benzotriazole (B), [9] and 1-aminobenzotriazole (15) [6] were prepared as described earlier. Other chemicals and solvents were purchased from commercial sources and were used without additional purification, unless mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…However, a completely different synthetic approach was used: 5,6-dicyano-1H-benzotriazole was prepared first, and then it was used to synthesize tetra- [39] and monotriazolophthalocyanines. [40] 1N-Amination of the latter compound and oxidation of the resulting amino derivative resulted in the generation of a dehydrophthalocyanine, which could be trapped in situ with several dienes to afford the corresponding Diels-Alder adducts. [41] The N-alkylation and N-arylation of triazoloporphyrins 2 are convenient routes to other porphyrinic derivatives.…”
Section: Dedicated To Professor Miha Tišler On the Occasion Of His 80mentioning
confidence: 99%